Continuities and Transformations in Identifying Gifted Students: The Role of Technology and Equity - Mutiu Owolabi Adesola; Sabina Nwakaego Obi; Faramade Esther Odunayo (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Gifted education has historically relied on narrow definitions of ability, often equating giftedness with high IQ scores and standardised test performance. While these measures provide clear benchmarks, they have been widely criticised for overlooking creativity, socio-emotional skills, and culturally diverse expressions of talent. The purpose of this research was to explore the continuities and transformations in gifted identification, with particular attention to the role of technology and equity. Specifically, the research asked how traditional markers of giftedness have persisted, how technological innovations have transformed identification practices, and what ethical and inclusivity challenges accompany these changes. Methodologically, the research adopted a qualitative desk research approach. A systematic review of scholarly publications, policy documents, and empirical studies published between 2015 and 2025 was conducted, complemented by key historical works. Thematic analysis was used to trace patterns of continuity, innovation, and ethical concern. The findings revealed that cognitive ability, creativity, problem-solving, and teacher judgment remain central in identification practices, reflecting their deep institutional embeddedness. At the same time, dynamic assessments, AI-driven adaptive platforms, and psychometric modelling represent a significant shift toward more individualised and process-oriented approaches. However, without safeguards, these innovations risk perpetuating inequities. It was concludes that gifted identification must be reframed as both a technical and ethical endeavour. Its contribution lies in offering a conceptual framework that balances innovation with equity, guiding policymakers and educators toward more inclusive and culturally responsive practices.